Contacts, Credibility and Common Knowledge : Their Influenceon Inflation Convergence. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper explains why sovereign issuers of reserve currencies do not use unexpected inflation to repudiate their foreign liabilities. Monetary restraint is exercised because of the fear that reserve users will switch to other currencies if an attempt is made to raise 'excessive' revenue. By the same reasoning, capital flight can serve as a deterrent to excessive money creation. It is shown that even without policy precommitment or aversion to inflation, the availability of alternative currencies can support an equilibrium with a finite, time consistent inflation rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet